2019
DOI: 10.1042/bsr20190290
|View full text |Cite
|
Sign up to set email alerts
|

A promising growth promoting Meyerozyma caribbica from Solanum xanthocarpum alleviated stress in maize plants

Abstract: Fungal endophytes are known to secrete a large array of secondary metabolites (phenols, flavonoids, indole acetic acid (IAA) etc.) that facilitate crops under stress conditions. Considering this, a potent plant growth promoting endophyte (SXSp1) from the spines and leaves of Solanum xanthocarpum L. has been isolated. The isolated strain ably secreted high quantities of indole-3-acetic acid, phenols and flavonoids. Also, it exhibited phosphate solubilization, siderophore and had 2,2 diphenyl-1-picrylhydrazyl (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Salinity stress affects the growth and metabolism of plants and causes a reduction in most growth indices. The decline in the growth parameters as a result of salinity stress was recorded in different investigations [ 50 , 51 , 52 ]. Our findings are in accordance with those documented by Zhang et al [ 53 ], who found that plant height, root length, shoot fresh and dry weight, and root fresh and dry weight were markedly decreased as a result of salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity stress affects the growth and metabolism of plants and causes a reduction in most growth indices. The decline in the growth parameters as a result of salinity stress was recorded in different investigations [ 50 , 51 , 52 ]. Our findings are in accordance with those documented by Zhang et al [ 53 ], who found that plant height, root length, shoot fresh and dry weight, and root fresh and dry weight were markedly decreased as a result of salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…These endophytic yeasts exude a range of secondary metabolites (phenols, flavonoids, abscisic acid (ABA), indoleacetic acid (IAA), etc.) to help the plant to overcome stress conditions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity greatly affects germination and vigor of the plant species, thus reduces the growth, development and yield of agricultural crops [20,31]. The presence of higher amounts of salts in soil may cause various metabolic and physiological disturbances [34,44], which can lead to low yield and quality of grains.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it affects plant's survival percentage, germination of seeds, and various morphological characteristics [41]. Nutritional disorders, ions toxicity, and nutrients imbalance in cytosol have been noticed in plants due to transport and dispersion of high salt contents [2,20]. Besides, it leads to oxidative stress at cellular and subcellular level that generates ROS (reactive oxygen species).…”
Section: Introductionmentioning
confidence: 99%